2021
DOI: 10.3390/genes12020157
|View full text |Cite
|
Sign up to set email alerts
|

Genome Analysis of Sable Fur Color Links a Lightened Pigmentation Phenotype to a Frameshift Variant in the Tyrosinase-Related Protein 1 Gene

Abstract: Sable (Martes zibellina) is one of the most valuable species of fur animals. Wild-type sable fur color varies from sandy-yellow to black. Farm breeding and 90 years of directional selection have resulted in a generation of several sable breeds with a completely black coat color. In 2005, an unusually chocolate (pastel) puppy was born in the Puschkinsky State Fur Farm (Russia). We established that the pastel phenotype was inherited as a Mendelian autosomal recessive trait. We performed whole-genome sequencing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
2
0
3
Order By: Relevance
“…The mating of same-color parents (Dark and Pastel) produced Dark offspring at 99.38%, and Pastel offspring at 98.35% of the time. A study on Pastel coat color inheritance in sables (Martes zibellina) also showed that the mating of both parents of Pastel color produced offspring with Pastel fur coats only [ 17 ]. The breeding results of green-eyed Pastel individuals in Ontario, Wisconsin in 1941 showed that using the same color for sire and dam resulted in the production of only green-eyed Pastel phenotypes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mating of same-color parents (Dark and Pastel) produced Dark offspring at 99.38%, and Pastel offspring at 98.35% of the time. A study on Pastel coat color inheritance in sables (Martes zibellina) also showed that the mating of both parents of Pastel color produced offspring with Pastel fur coats only [ 17 ]. The breeding results of green-eyed Pastel individuals in Ontario, Wisconsin in 1941 showed that using the same color for sire and dam resulted in the production of only green-eyed Pastel phenotypes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the same farm, when green-eyed Pastel was crossed with Dark individuals, both Dark and green-eyed Pastel color individuals were observed [ 19 ]. Similarly, offspring produced by crossbreeding Pastel and black sables followed the 1:1 ratio corresponding to Mendelian inheritance [ 17 ]. The heterozygous nature of alleles responsible for Pastel color was also reported by Eklund et al [ 26 ] and Shackelford [ 19 ] while crossing Ebony and Pastel color sire and dam respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Поскольку почти у всех пород и типов пушных зверей гетерозиготные особи, как правило, имеют худшую оценку по окраске, чем гомозиготные, то из стада при этом удалялись возможные носители мутантных генов окраски. При завозе отловленных соболей стандартной окраски (всего шесть самцов, из них пять с Камчатки) в 1991 году стали появляться звери с некоторым осветлением окраски (с бежевым, пастелевым и серым оттенками) (39)(40)(41).…”
unclassified
“…Присутствие в генотипе Pp доминантного мутантного гена может изменить тон окраски, при наличии двух мутантных генов PP их действие усилится. Кроме того, возможно влияние сопутствующих генов, в частности геновмодификаторов (41).…”
unclassified
See 1 more Smart Citation